Ability to Propose Optimal Prosthetic Rehabilitation can be Improved by Discussion between the Dentist and Radiation Oncologist Regarding Upstream Dosimetry - Rouers, Mélanie; Bornert, Fabien; Truntzer, Pierre; Dubourg, Sarah; Bourrier, Cyrielle; Antoni, Delphine; Noël, Georges (European Journal of Dentistry, 2019)
Objective Improvement of dental rehabilitation for patients who have undergone radiation therapy requires knowledge of the dose in the maxillary and mandible bones.Materials and Methods Forty-three patients with head and neck cancers underwent evaluation for dental rehabilitation before radiation treatment dosimetry. The delivered dose to the maxilla and mandible was determined. From the dose data in the literature, three levels of risk of implant failure were defined. According to the delivered doses, the authors calculated the percentage of patients who could be fully rehabilitated with an implant, as proposed by the dentist before radiation planning.Results Before dosimetry calculation, all of the completely edentulous arches and 94 partially edentulous (PESs) sextants could be optimally rehabilitated. After dose calculation, among the 14 arches of 7 patients who were completely edentulous, according to the mean and maximal delivered doses, 11 arches (78.6%) and 7 arches (50%) could receive an optimal prosthesis, respectively. For the three patients, who were PESs but with one arch that was completely edentulous, according to the mean and maximal delivered doses, one arch for each dose condition could receive an optimal prosthesis. Among the 94 PESs sextants, according to the mean and maximal delivered doses, 41 (43.6%) and 24 (25.5%) sextants could receive an optimal prosthesis, respectively.Conclusion By determining the sites of implantation before dosimetry, the radiation oncologist could shield specified areas, potentially improving the possibilities for dental rehabilitation. The dialogue between the dentist and the radiation oncologist can improve the possibilities for implants and decrease the risk of unsafe implantation.
Keywords: dental care; dental implant; dental prosthesis; head and neck cancer; treatment planning